Human rights and migratory policy. Arbitrary discrimination in Chile’s border control (Polis (Santiago), 2019)
Human rights have to be considered within migratory policies of modern States. However, this subject is stressed with the sovereignty principle, which permits control at these State’s borders. When border control violates the human rights of migrant population this is considered arbitrary discrimination. The aim of this article is to identify the legal gaps and also the legal guarantees that exist in diverse legislative instruments and law projects regarding migration, that allow the avoidance of arbitrary discrimination at the border control, in special in the northern part of the country. The research was conducted through documental analysis and interviews with experts. The results demonstrate that, even though there are improvements in several subjects -such as the creation of a new institutionalization and the recognition of human rights in law projects-, they don’t include neither they give an effective solution to the legal gap that facilitates arbitrary discrimination.
Keywords: borders; arbitrary discrimination; migration policy; human rights.